IDENTIFYING AND DIAGNOSING THE GAP IN APPLYING ARTIFICIAL INTELLIGENCE TECHNIQUES SCALE IN MANAGING HIGH-PERFORMANCE SPORTS ORGANIZATIONS - Aseel H. Obaid; Naeema Zeidan Khalaf (Sport Scientific And Practical Aspects, 2025)
This study seeks to evaluate the technician in the Department of Sports and School Activity in the General Directorate of Education of Baghdad / Al-Rusafa II, according to the requirements of the standard of artificial intelligence techniques in order to diagnose and identify the gap between the technical performance of this section with the requirements of the standard, identify the causes of the gap and propose effective solutions for it. The checklist was used to collect data and information according to the scale of artificial intelligence technologies with five axes (expert systems, virtual reality, smart agents, information technologies, and process automation). The Department of Sports and School Activity in the General Directorate of Education of Baghdad / Al-Rusafa II (case study) have a clear perception of the importance of the measure of artificial intelligence techniques, but the absence of financial and technical capabilities prevents the adoption of this measure in the management of the department, in addition to the lack of management of the department of an administrative unit to follow up the functional work And technology and studying the causes of deviation and the procedures to be followed for the purpose of controlling all factors affecting artificial intelligence techniques, and by examining the results of this study obtained from the checklists, it can be indicated that there are weaknesses in all the requirements that must be available in the sports and school activity section and according to the requirements of the intelligence techniques scale With regard to the axis of expert systems and the axis of smart agents, the percentage of matching dolls was (0%) and the gap for non-conformity amounted to (1). As for the axis of virtual impact, it is not less important than them, as the amount of the gap amounted to (0.9), but the amount of the gap for the axes of information technology and process automation is (0.3), which indicates that the Department of Sports and School Activity applies in its work to most of the paragraphs of these two axes to the requirements of the scale of artificial intelligence technologies.